Recruitment and survival of native annual Trifolium species in the highlands of Ethiopia - Dauro, D.; Mohamed-Saleem, M.A.; Gintzburger, G. (Wiley, 1997)
Germination and survival of indigenous annual Trifolium species were studied. Seedlings naturally emerging in the field and from sown seeds in pots were regularly counted and uprooted, and survival was studied by monitoring colour-coded seedlings. Differences in recruitment of Trifolium species were strongly related to the rainfall pattern. In the fallow (crop) lands, no seedling survived the dry season between the short and main rainy periods during the year, while in the natural pasture, 8 percent of the seedlings survived into the main growing (rainy) season. Occasional rains occuring in the dry period (between the two rainy periods) also induced successions of germination and seedlings death, and therefore depleted the soft seed reserve in the soil by the beginning of the main growing season. As temperature fluctuations were minimal during the main rainy season, the rate of seed softening was low, affecting new germinations. This had a significant impact on the quality of the natural pastures on which livestock in the highlands are dependent.